Electronic JPJ theory test taking / Wong Yuan Khee Wet - Wong, Yuan Khee Wet (2003)
This project is a step towards realizing our beloved Prime Minister vision of achieving a paperless government in the near future. The existing procedure in taking JPJ theory test has shortcoming that can be improve by this proposed electronic test taking. The electronic JPJ theory test taking is focus on the superiority in the questions randomness, security and reliability. In the new procedure, candidate will have to take the JPJ test using computers that are connected in a LAN environment. The computers that are connected in a LAN environment. The computers are divide by cubicles thus unable fot the candidate to perform fraud. Questions from the test will be randomly arrange from the existing questions sets. The probability of getting the same arrangement of question in two sets of questions is near zero. Even though all the test taking will be done electronically but the manual test taking will be allowed under certain condition such age barrier. After the test is ended the answers will be automatically checked and result will be calculated in real time. The candidates can get their results immediately from the counter.This safe time of waiting for the results to be announce. Thus candidate who failed the test can retake the test on the same day compare to existing procedure where failed candidates have to retake the test on the another day. One more feature that's worth mentioning is that the results will be directly inserted into the database. This will prevent the result from being tampered with or error cause by human handling of the results.